2021
DOI: 10.1021/acs.jpca.1c01835
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Photodetachment Dynamics of the OH(C2H4) Anion Complex

Abstract: Photoelectron–photofragment coincidence (PPC) measurements on OH–(C2H4) anions at a photon energy of 3.20 eV revealed stable and dissociative photodetachment product channels, OH–C2H4 + e– and OH + C2H4 + e–, respectively. The main product channel observed was dissociation to the reactants (>67%), OH + C2H4 (v = 0, 1, 2) + e–, where vibrational excitation in the C–H stretching modes of the C2H4 photofragments corresponds to a minor channel. The low kinetic energy release (KER) of the dissociating fragments is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…In summary, we have found that photodetachment of ground states. This interpretation of the data is similar to previous studies of hydroxyl radical reactions 27,36 and the reaction of F + CH 3 OH. 28 Water stretch excitation in photodetachment was found to promote dissociation of the nascent complex, while bend excitation was seen predominantly in long-lived neutral complexes.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In summary, we have found that photodetachment of ground states. This interpretation of the data is similar to previous studies of hydroxyl radical reactions 27,36 and the reaction of F + CH 3 OH. 28 Water stretch excitation in photodetachment was found to promote dissociation of the nascent complex, while bend excitation was seen predominantly in long-lived neutral complexes.…”
supporting
confidence: 91%
“…In summary, we have found that photodetachment of CH 3 O – (H 2 O) at a photon energy of 3.20 eV yields both direct and resonance-mediated mechanisms for the formation of vibrationally excited H 2 O + CH 3 O + e – products in addition to a significant yield of H 2 O + CH 3 O + e – in the vibrational ground states. This interpretation of the data is similar to previous studies of hydroxyl radical reactions , and the reaction of F + CH 3 OH . Water stretch excitation in photodetachment was found to promote dissociation of the nascent complex, while bend excitation was seen predominantly in long-lived neutral complexes.…”
supporting
confidence: 89%
“…Their study established that CH 4 , when in the OH – ·CH 4 complex, is slightly distorted relative to isolated CH 4 , since vibrational excitation of CH 4 was evident in the photoelectron spectrum. A similar study was conducted on the OH – ·C 2 H 4 ion–molecule complex . Their results provided insight into the dynamics of the entrance channel of the abstraction reaction.…”
Section: Neutral Atmospheric Reaction Complexes Studied By Detachment...mentioning
confidence: 99%
“…A similar study was conducted on the OH − •C 2 H 4 ion−molecule complex. 136 Their results provided insight into the dynamics of the entrance channel of the abstraction reaction.…”
Section: Neutral Atmospheric Reaction Complexes Studied By Detachment...mentioning
confidence: 99%
“…Kinetic experiments have been performed to obtain information on the rate coefficients and their dependence on temperature and pressure, and kinetic and photochemical investigations to derive product branching fractions have also been reported. Additionally, theoretical calculations have been carried out to derive the relevant potential energy surface (PES) and to obtain a theoretical estimate of the rate coefficients through high-level ab initio electronic structure and kinetic (statistical) calculations. According to these studies, the OH + C 2 H 4 reaction can proceed through two different mechanisms, that is, either by the H-abstraction mechanism, leading to the formation of a water molecule and the vinyl radical (C 2 H 3 ), or by the addition mechanism of the OH radical to the CC double bond of ethylene. While the direct abstraction process exhibits a sizeable entrance energy barrier, the addition process appears to be barrierless and is characterized by the initial formation of a pre-reactive van der Waals complex, which leads to the formation of the C 2 H 4 OH (2-hydroxyethyl) covalently bound radical intermediate through a submerged barrier.…”
Section: Introductionmentioning
confidence: 99%